2021
DOI: 10.1039/d0ta09226f
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective photocatalytic conversion of methane to liquid oxygenates over silicomolybdic-acid/TiO2under mild conditions

Abstract: H4SiMo12O40/TiO2 was demonstrated to be an excellent catalyst for photocatalytic methane oxidation to liquid oxygenates. This provides the first successful example of polyoxometalate-based catalysts for photocatalytic methane conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Methane (CH 4 ) is the main component of natural gas and combustible ice, whose large-scale conversion into value-added chemicals is conducted via steam reforming into syngas (CO and H 2 ) and subsequent Fischer–Tropsch synthesis. , However, such a multistep technique suffers from a high cost to reach an operation temperature of 800–900 °C. Distinct from traditional thermal catalysis, photocatalysis is advantageous for activating inert molecules owing to the facile production of free radicals, which could easily initiate the dissociation of C–H bond in CH 4 . However, so far, only ultraviolet light can be utilized for CH 4 conversion in most studies. Therefore, it is still highly desirable to develop a visible-light driven process for direct and highly efficient conversion of CH 4 .…”
mentioning
confidence: 99%
“…Methane (CH 4 ) is the main component of natural gas and combustible ice, whose large-scale conversion into value-added chemicals is conducted via steam reforming into syngas (CO and H 2 ) and subsequent Fischer–Tropsch synthesis. , However, such a multistep technique suffers from a high cost to reach an operation temperature of 800–900 °C. Distinct from traditional thermal catalysis, photocatalysis is advantageous for activating inert molecules owing to the facile production of free radicals, which could easily initiate the dissociation of C–H bond in CH 4 . However, so far, only ultraviolet light can be utilized for CH 4 conversion in most studies. Therefore, it is still highly desirable to develop a visible-light driven process for direct and highly efficient conversion of CH 4 .…”
mentioning
confidence: 99%
“…Together, these observations rationalize why studies with a focus on the production of value-added chemicals from methane oxidation with oxygen frequently employ a CH 4 /O 2 ratio much higher than that required stoichiometrically. 7 , 22 , 75 78 Methane oxidation with oxygen can result in a range of useful value-added products, including ethane, methanol, and formaldehyde. 12 The stoichiometry of reactions between methane and oxygen ranges from 1/2 CH 4 /O 2 (total oxidation to CO 2 ) to 4/1 CH 4 /O 2 (oxidative coupling to ethane), 12 but many studies with a focus on production of value-added chemicals from methane oxidation with oxygen employs a higher CH 4 /O 2 ratio than that required stoichiometrically for the formation of desired/observed products, often with over 10 times more CH 4 than O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous suggestions about the activation of the highly symmetrical and stable molecule methane. First, it was suggested that CH 4 was able to be directly oxidized by photoexcited holes (e.g., in the form of O – species) in the valence band (VB) of TiO 2 or TiO 2 -based materials to form the CH 3 • radical and OH – , or H + . , Also, Yoshida et al extrapolated knowledge from thermal catalysis and suggested that O – (photoexcited hole) directly extracts a H • radical from CH 4 . In the case of OH – , the electron density mainly resides on the oxygen and therefore can be regarded as a “filled” hole in/near the VB.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been confirmed as an effective catalyst in organic pollutant photodegradation and hydrogen generation with UV illumination owing to its advantages of chemical inertness, low cost, and being harmless with high reactivity. 25 However, pure TiO 2 has a large band gap and poor utilization efficiency of visible light, limiting its practical application. To solve this problem, a number of efforts have been made to couple TiO 2 with semiconductor materials that possess a narrow band gap, especially copper sulfide (CuS), for developing high-performance TiO 2 based catalysts.…”
Section: Introductionmentioning
confidence: 99%